Legal Protection of Brand Rights for Micro, Small, Medium Business Product (MSMES) in Medan Selayang District, Medan City - Puspa Melati Hasibuan; Zulfi Chairi; Aflah Aflah (International Journal of Social Service and Research, 2022)
This study aims to determine why registration of brand rights for goods or services is important for MSME actors. The other purpose is to determine the legal consequences for MSME products whose brand rights are not registered and the linkage of brand rights as economic rights for MSME. This study is normative juridical research using the qualitative descriptive analysis method. The study is supported by primary data from the interview and secondary data, which are primary, secondary, and tertiary legal material. The study found that brand right is a differentiating identity that helps MSMEs get loyal consumers. Brand rights can also be an effective marketing method and a form of legal protection from plagiarism. Brand rights can also give economic value because they can be sold or transferred to other individuals or legal entities as a franchise. This study helps to understand MSME actors' Brands so that the interest of MSME actors to register their brands' increases. The increase of interest from MSME actors can be a momentum to guarantee legal protection for more MSME actors and products.